Vinyl nosylates as partner in copper and silver co-catalyzed Sonogashira cross-coupling reactions. Issue 50 (13th December 2018) - Cheval, Nicolas P.; Hoffmann, Barbara; Dikova, Anna; Sirindil, Fatih; Bertus, Philippe; Blanc, Aurélien; Weibel, Jean-Marc; Pale, Patrick
Abstract: Vinyl nosylates, readily obtained from β-dicarbonyl derivatives, could be efficiently engaged in Sonogashira cross-coupling reactions, either cocatalyzed by copper or silver salts. The para -nitrobenzenesulfonate (nosylate) group allows this coupling to be performed under very mild conditions (room temperature). These new leaving group and mild conditions could be applied to the synthesis of acetylenic coumarinyl derivatives and to the total synthesis of an acetylenic monoterpene natural product, named cleviolide. Graphical abstract: